The Development of Pandanus Salted Egg Product with White Clay Filler of Occupation Group at Thanonyai Sub-district, Mueang District, Lop Buri Province - Puangpejara, Kulchalee; Kamnuanchai, Sopit; Srikanjanarak, Saowanee; Phermpiam, Panuphan (Community and Social Development Journal, 2020)
The purposes of this participation action research were to: 1) study the state and problems of the development of pandanus salted egg product with white clay filler of Occupation Group at Thanonyai Sub-district, Mueang District, Lop Buri Province; and 2) develop pandanus salted egg product with white clay filler of Occupation Group at Thanonyai to be distinctive product. The samples used in the study, selected by purposive sampling, were 30 members affiliated to pandanus salted egg product with white clay filler of Occupation Group, two community leaders, two academic staff in food science and marketing, and 400 product consumers, drawn by accidental sampling. The Mixed Method Research (MMR) including observation, in-depth interview, questionnaire, focus group and experiment was employed for data collection. The quantitative data were systematically analyzed to determine percentage, mean and standard deviation, and also qualitative data to capture categories using a content analysis and concluding the experimental results. According to the results of the study, the serious problems of pandanus salted egg product with white clay filler were too salty taste, lack of pandanus aroma, and lack of developing its own unique brand, therefore it did not attract consumers and tourists to buy as souvenirs. As for the experimental work, using raw materials and process according to the advice of the food science academic staff to develop pandanus salted egg product with white clay filler to be distinctive product, the findings revealed that: 1) pandanus salted egg product with white clay filler had a mellow taste, and not too salty; 2) the distinctive feature of product was the aroma of pandanus leaves penetrating into its meat; and 3) brand name should refer to source of production; its logo and slogan should be attractive customers and be easy to remember.